PENGEMBANGAN MEDIA DIGITAL INTERAKTIF BERBASIS CANVA PADA PEMBELAJARAN MATEMATIKA MATERI BANGUN DATAR KELAS IV SD - Musthofiah, Afifatul; Wardana, Muhammad Yusuf Setia; Sulianto, Joko (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT The limited use of visual media in mathematics instruction leads to low student understanding of plane geometry. This study aims to develop interactive digital learning media based on Canva that meet the criteria of validity, practicality, and effectiveness for fourth-grade elementary school students. The research employed a research and development approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation, teacher and student response questionnaires, and learning achievement tests. The results show that the developed media achieved very high levels of validity and practicality based on evaluations by experts and users. The implementation of the media also had a positive impact on student learning outcomes, as indicated by an increase in average scores from the pretest to the posttest. The media helped students understand the characteristics and properties of plane shapes through more engaging visual presentations and interactive features. In addition, the use of Canva made it easier for teachers to present instructional materials in a systematic and efficient manner. Therefore, Canva-based interactive digital media are appropriate to be used as a supporting tool for mathematics learning in elementary schools. ABSTRAK Keterbatasan penggunaan media visual dalam pembelajaran matematika menyebabkan rendahnya pemahaman siswa terhadap materi bangun datar. Penelitian ini bertujuan mengembangkan media digital interaktif berbasis Canva yang memenuhi kriteria valid, praktis, dan efektif untuk siswa kelas IV sekolah dasar. Penelitian menggunakan metode penelitian dan pengembangan dengan model ADDIE yang mencakup tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Data diperoleh melalui validasi ahli, angket respons guru dan siswa, serta tes hasil belajar. Hasil penelitian menunjukkan bahwa media yang dikembangkan memperoleh tingkat validitas dan kepraktisan yang sangat tinggi berdasarkan penilaian para ahli dan pengguna. Penerapan media juga berdampak positif terhadap hasil belajar siswa, yang ditunjukkan oleh peningkatan nilai rata-rata dari pretest ke posttest. Media ini membantu siswa memahami karakteristik dan sifat bangun datar melalui penyajian visual dan interaksi yang lebih menarik. Selain itu, penggunaan Canva mempermudah guru dalam menyajikan materi secara sistematis dan efisien. Dengan demikian, media digital interaktif berbasis Canva layak digunakan sebagai sarana pendukung pembelajaran matematika di sekolah dasar.